Le rôle du parler populaire dans la structuration du discours médiatique de la presse algérienne lors d’un événement sportif - Fateh Chemerik (Communication)
The author finds in the coverage of the 2009 Egypt–Algeria soccer match a number of changes in the journalistic practices of the Algerian French-language press. Popular language was powerfully present on newspaper front pages. The author suggests that the Algerian French-language press coconstructed the soccer event to promote a kind of “Algerianness” in opposition to the Arabness “self-proclaimed” in the Cairo media. The analysis is based on 97 headlines from four Algerian newspapers—two sports papers and two general-interest ones—published between November 14 and 19, 2009. The study also draws on semistructured interviews of four newspaper managers, four editors, and eight journalists conducted between 2013 and 2020.